2014
DOI: 10.5858/arpa.2013-0691-ra
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Preanalytical Factors Affecting Molecular, Protein, and Morphological Analysis of Formalin-Fixed, Paraffin-Embedded (FFPE) Tissue: How Well Do You Know Your FFPE Specimen?

Abstract: Based on the literature evidence, the molecular, proteomic, and morphological endpoints can be altered in formalin-fixed, paraffin-embedded specimens by suboptimal processing conditions. While the direction and magnitude of effects associated with a given preanalytical factor were dependent on the analyte (DNA, RNA, protein, and morphology) and analytical platform, acceptable conditions are highlighted, and a summary of conditions that could preclude analysis is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
195
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(210 citation statements)
references
References 140 publications
5
195
0
4
Order By: Relevance
“…Soft tissues can be separated from sclerotic tissues and placed in different blocks. In most bone materials with metastatic lesion recognition, the tumor part usually does not require decalcification because most tumors damage the bone structure (103,104).…”
Section: Special Material: Bonementioning
confidence: 99%
See 1 more Smart Citation
“…Soft tissues can be separated from sclerotic tissues and placed in different blocks. In most bone materials with metastatic lesion recognition, the tumor part usually does not require decalcification because most tumors damage the bone structure (103,104).…”
Section: Special Material: Bonementioning
confidence: 99%
“…In a material that has been decalcified in an experimental study conducted in Colorado University, it was reported that as basophilia increases in the bone trabeculae, the reliability of molecular treatment also increases. This is related to the eosinophilic appearance of the fully decalcified bone trabecula while basophilia reflects less extensive decalcification (103,104).…”
Section: Special Material: Bonementioning
confidence: 99%
“…Formalin fixation and paraffin embedding was performed as previously described (12). Five micron thick sections were cut from each paraffin block and stained with haematoxylin and eosin (H and E) staining.…”
Section: Histopathologymentioning
confidence: 99%
“…1-3). [1][2][3] Effects attributable to pre-analytical factors can be severe, resulting in misdiagnosis 4 and false discovery of biomarkers of disease, 5,6 and also both extensive and elusive, as 48%-58% of biobanked tissue collected and stored using institution-approved SOPs was deemed unfit for RNA analysis. 7,8 Thus, the availability of human biospecimens of sufficiently high quality continues to be a pressing need of the medical research community.…”
mentioning
confidence: 99%
“…However, in most instances, SOPs are institution-specific, which can confound analysis of biospecimens collected at different hospitals or those obtained from different biobanks or biorepositories. Use of institution-specific SOPs may also preclude external validation of research findings, as well as meta-analysis efforts employed by both regulatory organizations, such as the United States Food and Drug Administration (USFDA) and the European Medicines Agency (EMA), and scientific organizations that aim to identify pre-analytical factors and their effects [1][2][3] or potential markers of biospecimen quality. 9 While there is a real and present need for a more global method of standardization and validation, universal adoption of a single collection of SOPs is impractical due to the different logistical and financial constraints associated with individual facilities.…”
mentioning
confidence: 99%